Pengaruh Harga Produk, Kualitas Produk dan Lokasi Pada Keputusan Pembelian Wedrink di Surakarta - Risma Nur Pratiwi; Intan Yunitasari; R Taufiq Nur Muftiyanto; Rayhan Gunaningrat (Master Manajemen, 2024)
At present, a growing number of consumers exhibit discerning behavior in their consumption habits, carefully selecting the products they desire and require. Consequently, companies and entrepreneurs need to demonstrate increased intelligence and innovation in crafting products aligned with consumer preferences. This study aim to investigate and assess the impact of price product, product quality, and location on the purchasing decisions of WeDrink customers in Surakarta. Data collection involved the distribution of questionnaires to respondents who had previously bought WeDrink products in Surakarta. The sample size for this study comprised 125 respondents. Multiple linear regression analysis was employed as the data analysis method, utilizing SPSS 26 software. The research findings are categorized into four main points. First, the price of the product doesn’t significantly affect purchasing decisions for WeDrink in Surakarta. Second, product quality significantly influences the purchasing decisions of WeDrink consumers in Surakarta. Third, the location also holds significant sway over WeDrink purchasing decisions in Surakarta. Fourth, the combined impact of product price, product quality, and location influences the purchasing decisions of WeDrink consumers in Surakarta.